Pengaruh Konsentrasi Surfaktan dan Perbandingan Volume Emulsi dengan Volume Fasa Eksternal Pada Ekstraksi Ion Merkuri Menggunakan Teknik Emulsi Membran Cair - Hidayah, Nurul; Hamzah, Baharuddin; Ningsih, Purnama (Universitas Tadulako, 2017)
Mercury ion extraction has been done using emulsion liquid membrane technique a research. The aim of the study is to determine the optimal conditions at the extraction process of mercury ion with research variables, namely variations of the surfactant concentration and the volume ratio of emulsion and external phase (Ve:Veks). In this study, the sample was 20 mg/L of Hg2+ ions in concentration. The concentration of mercury ions remaining in the sample after extraction were analyze using a UV-Vis Spectrophotometer at a wavelength of 490 nm using ditizon as complexation. The optimum condition far varying concentrations surfactant was 2% and the volume ratio of emulsion (Ve) and external phase (Veks) was 1:5 with the percentage of extraction respectively 47.65% and 56.80%.